Influências dos elementos climáticos sobre pessoas portadoras de fibromialgia - Menezes, Vera Conrad de (2023)
The relationship between climate and health-disease conditions is widely known in the scientific literature. However, most are explorations based on understanding the impacts of climate on infectious and parasitic diseases. More recently, these studies have been expanded to understand chronic conditions, such as cardiovascular and mental illnesses. However, investigations into the relationship between climate and rheumatic diseases, especially fibromyalgia, are still little explored and fragmented. The aim of this study is to investigate the possible influences of climatic elements on patients with fibromyalgia. The methodology used was a systematic review on scientific platforms from the controlled descriptors of “climate and fibromyalgia”, in English, Portuguese and Spanish, in the time period from 1990 to 2023. The first phase of the search allowed the selection of 51 articles. These articles were then evaluated in terms of their abstracts, objectives, methodology and results. This evaluation resulted in 28 articles associated with the theme. The next step was to read these 28 articles in full. This led to the exclusion of another 10 articles that did not respond to the research question? Finally, the remaining 18 articles were analyzed according to their results, ability to assess the relationship between climate and fibromyalgia, and scientific relevance of the publication the results showed inconclusive outcomes for the relationship between climatic factors and fibromyalgia, with a predominance of observational epidemiological studies. No experimental study was found, with control of climatic and symptomatic variables at the same time. There were still few studies of Geography and Climatology applied to understanding the relationship between climate factors and rheumatic diseases, including fibromyalgia. The researchers agree that more objective and in-depth studies should be performed out on this thematic. Fibromyalgia is a relatively new disease, still unknown by society, and little explored by geographic science. This study demonstrates the relevance of understanding the impacts of climatic factors on rheumatic diseases, in particular the impacts on people with fibromyalgia.